2016
DOI: 10.1182/blood-2016-03-704460
|View full text |Cite
|
Sign up to set email alerts
|

A clinically relevant in vivo zebrafish model of human multiple myeloma to study preclinical therapeutic efficacy

Abstract: Key Points MM cell lines and primary MM cells can be engrafted and grown in vivo in Casper zebrafish larvae. The zebrafish MM in vivo xenograft model can be used as a pretreatment drug-sensitivity prediction platform for MM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 13 publications
(12 reference statements)
0
58
0
Order By: Relevance
“…Therefore, zPDX models are more suitable for high‐throughput studies, which can yield greater statistical power and possibly identify previously undetectable subclones (e.g., drug‐tolerant subclones) . Furthermore, zPDX models could better preserve information of the parental tumors as patient‐derived cells could be used immediately after cell dissociation rather than at Passage 3 or later, which is common for murine PDX tumors . Recent studies have also suggested a variety of alternatives for model selection, and some have potential to become next‐generation preclinical cancer models.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Therefore, zPDX models are more suitable for high‐throughput studies, which can yield greater statistical power and possibly identify previously undetectable subclones (e.g., drug‐tolerant subclones) . Furthermore, zPDX models could better preserve information of the parental tumors as patient‐derived cells could be used immediately after cell dissociation rather than at Passage 3 or later, which is common for murine PDX tumors . Recent studies have also suggested a variety of alternatives for model selection, and some have potential to become next‐generation preclinical cancer models.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…These authors were the first to show in a retrospective study that zPDXs can be a predictive tool for co-clinical assays. In this study, zPDXs were treated with bortezomib and lenalidomide, and showed a response equivalent to patient's clinical outcome: sensitive tumors responded, whilst metastatic tumors did not, similarly to what was observed in patients (n = 6 patients) [112]. Subsequent work from Wu J.Q.…”
Section: Zebrafish Patient-derived (Zpdx)-avatarsmentioning
confidence: 74%
“…Since then, several zebrafish xenograft studies have been developed mostly with commercially available cell lines, derived from a wide range of cancer types, such as breast cancer, leukemia, lung cancer, CRC, pancreatic cancer, stomach cancer, glioblastoma, and melanoma (Table S1). This model has been successfully established to investigate several hallmarks of cancer, in particular angiogenesis [104,[106][107][108][109][110][111][112], cancer cell invasion/extravasion [113][114][115], and micrometastasis formation [106,114,116] (Table S1). In addition, there are already several studies that use the zebrafish xenograft model in the process of drug discovery and pre-clinical evaluation of different types of therapies, such as chemotherapy, radiotherapy [117,118] and biological therapies [106] (Table S1).…”
Section: Pioneersmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, various human tumor cell lines, including melanoma, glioma, hepatoma, lung cancer, pancreatic cancer, ovarian carcinomas, breast cancer, prostate cancer, retinoblastoma, and leukemia, have been xenotransplanted into zebrafish 18 to study several aspects of tumorigenesis, like tumor cell migration, angiogenesis, extravasation, and micrometastases [19][20][21][22][23] . Most importantly, proof-of-concept studies have suggested that xenogeneic tumor transplant models using zebrafish embryos can be used as a screening platform to identify novel therapeutic compounds and approaches [24][25][26][27] . However, long-term, high resolution, timelapse images of such transplanted tumor cells are lacking, and their behavior in circulation has not been continuously monitored.…”
mentioning
confidence: 99%